(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Global warming is currently an issue that is widely discussed of both the accounting literature and others. The topic of environmental performance is gaining increasing attention from academics and politics when it is associated with each country’s policies regarding environmental damage. Purpose: This article to investigate both the direct and indirect the effect of green innovation and firm value on financial performance as mediating variable Design/methodology/approach: The samples in this study are applied using purposive sampling ad obtained total sample of PROPER participating companies listed in Indonesia Stock Exchange during the year of 2012-2018. The data used in this study are secondary data obtained from annual report. Companies are listed on the Indonesia Stock Exchange in mining industry in 2012-2018. The variable green innovation was measured by using PROPER, the financial performance was measured by ROA and the firm value were measured by Tobin’s Q. Data processing uses SEM-PLS with WarpPLS 6.0 with the consideration that SEM-PLS is a reliable tool for testing predictive models. Several studies using capital market data in Indonesia have found data with abnormal distribution, so data using PLS is appropriate. Result of the study: The authors find that the green innovation has a positive effect on the firm value and financial performance full mediate the effect green innovation and firm value. Research limitations: this article only examines green innovation using the PROPER measure while the green innovation measure is thought to be related to company value such as ISO 14001, content analysis is not discussed at all in this article and the research sample is limited to mining companies. This scope may not be able to describe the overall conditions in Indonesia. Originality/value: This study comprehensively examines both direct and indirect effect of green innovation with financial performance and firm value, which is rarely examined in extant studies.